Pengaruh Kepemimpinan Kepala Sekolah dan Lingkungan Kerja terhadap Kinerja Guru SD di Majalaya Karawang - Alin Hermawan; Bambang Ismaya; Abduloh Abduloh; Saepul Ma’mun; Endi Rochaendi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to analyze the influence of principals’ leadership styles and work environment on the performance of public elementary school teachers in Majalaya District, Karawang Regency, both partially and simultaneously. A quantitative approach was employed using a survey method and multiple linear regression analysis. The sample consisted of 92 teachers selected through proportional random sampling. Data were collected using a closed-ended Likert-scale questionnaire that had been tested for validity and reliability. Descriptive analysis showed that the principal’s leadership style and teacher performance were rated as